Variation - Normen - Identitäten - Lenz, Alexandra N.; Plewnia, Albrecht (Germanistische Sprachwissenschaft um 2020, 2018)
The description and analysis of linguistic variation is one of the fields that has recently received much attention in German linguistics. This volume shows in a synopsis of different approaches from attitude to language contact research, how to understand variation along different norm orientations of speakers and as a result of identity constructions.